2021
DOI: 10.1186/s13020-021-00529-9
|View full text |Cite
|
Sign up to set email alerts
|

A correlational study of Weifuchun and its clinical effect on intestinal flora in precancerous lesions of gastric cancer

Abstract: Background Weifuchun (WFC), a Chinese herbal prescription consisting of Red Ginseng, Isodon amethystoides and Fructus Aurantii, is commonly used in China to treat a variety of chronic stomach disorders. The aim of the paper was to determine the effect of WFC on intestinal microbiota changes in precancerous lesions of gastric cancer (PLGC) patients. Methods PLGC patients of H. pylori negative were randomly divided into two groups and received either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Three studies [ 29 , 32 , 35 ] used the method of random number tables. Yanqin Bian [ 34 ] used the method of Computer-generated randomization, but the other studies [ 21 – 28 , 30 , 31 , 33 ] just described “randomization”. Three studies reported “double-blind” methods [ 25 , 31 , 34 ], and the study of Yanqin Bian [ 34 ] was the only one that elaborated on how to blind and allocate concealment.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 29 , 32 , 35 ] used the method of random number tables. Yanqin Bian [ 34 ] used the method of Computer-generated randomization, but the other studies [ 21 – 28 , 30 , 31 , 33 ] just described “randomization”. Three studies reported “double-blind” methods [ 25 , 31 , 34 ], and the study of Yanqin Bian [ 34 ] was the only one that elaborated on how to blind and allocate concealment.…”
Section: Resultsmentioning
confidence: 99%
“…Taking WFC as an example, compared with vitacoenzyme (Vit), the total effective rates of the WFC and Vit groups in alleviating the degree of atrophy were 80.00% and 23.33%, respectively. The total effective rates of relieving IM in the WFC and Vit groups were 73.33% and 26.67%, respectively[ 16 ]. Notably, primary outcome measures, such as overall survival and 5-year survival rates, were employed in majority of these trials.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, angiogenesis, and proliferation are the three most important histological features of the transformation from GPL to GC[ 12 - 14 ]. Chronic inflammation is the core driver of GC[ 15 , 16 ]. Inflammation promotes angiogenesis, and its progression depends on the speed of angiogenesis[ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have shown that Citrus aurantium also has potential therapeutic effects on cardiovascular disease and cancer [ 19 ]. Weifuchun tablet is a proprietary Chinese medicine containing three Chinese herbs, namely, red ginseng, Isodon amethystoides, and Citrus aurantium , to relieve precancerous lesions of gastric cancer by regulating intestinal microbial balance and treating atrophy and intestinal metaplasia (IM) [ 20 ]. The above studies show that Citrus aurantium is a good anticancer herbal medicine, but the therapeutic effect and mechanism of action of Citrus aurantium on NSCLC have not been reported yet and deserve further study.…”
Section: Introductionmentioning
confidence: 99%